2017
DOI: 10.1021/acs.jpca.6b05168
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study on Reaction Pathways Leading to CO and CO2 in the Pyrolysis of Resorcinol

Abstract: Possible pathways for the pyrolysis of resorcinol with the formation of CO and CO as final products were proposed and evaluated using ab initio calculations. Our experimental study revealed that large quantities of CO are generated in the pyrolysis of 1,3-dihydroxybenzene (resorcinol), while the pyrolysis of the dihydroxybenzene isomers 1,2-dihydroxybenzene (catechol) and 1,4-dihydroxybenzene (hydroquinone) produces little CO. The fate of oxygen atoms in catechol and hydroquinone was essentially the formation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…The counter product was hypothesized to be cyclopentadiene 97 or a C5H4 species. 99 Only recently could Gerlach et al show conclusively using PEPICO detection 98 that resorcinol decarboxylation proceeds over acyclic C5H6 species, such as 1,2,4-pentatriene, Eand Z-1-butyne-3-ene, and 1-butyne-4-ene at moderate reactor temperatures (Figure 8a). Franck-Condon spectral modelling and high-level adiabatic ionization energy calculations yielded a definitive assignment of the C5H6 isomers.…”
Section: Decomposition Of Lignin Model Compoundsmentioning
confidence: 99%
“…The counter product was hypothesized to be cyclopentadiene 97 or a C5H4 species. 99 Only recently could Gerlach et al show conclusively using PEPICO detection 98 that resorcinol decarboxylation proceeds over acyclic C5H6 species, such as 1,2,4-pentatriene, Eand Z-1-butyne-3-ene, and 1-butyne-4-ene at moderate reactor temperatures (Figure 8a). Franck-Condon spectral modelling and high-level adiabatic ionization energy calculations yielded a definitive assignment of the C5H6 isomers.…”
Section: Decomposition Of Lignin Model Compoundsmentioning
confidence: 99%
“… 17 Based on computations, a biradical reaction pathway was proposed. 18 By using in situ photoelectron photoion coincidence (PEPICO) methods, we found compelling spectroscopic evidence ( vide infra ) that the resorcinol decomposition mechanism is dominated by a retro-Diels–Alder reaction to produce CO 2 and C 5 H 6 isomers (R1) instead or it leads to two highly reactive ketenes species (R1). 18,19 Furthermore, the three benzenediols share the same reaction to form cyclopenta-2,4-dien-1-ol (C 5 H 6 O) and 2,4-cyclopentadiene-1-one (C 5 H 4 O), initiated by CO loss in a phenolic keto–enol tautomerism pathway (see R2 for an overview).…”
Section: Introductionmentioning
confidence: 99%
“…However, their kinetics calculations suggested that decarboxylation is not feasible, at odds with their experimental data. 20 Among the three benzenediols, Ormond et al found that only the meta isomer resorcinol yields C5H6 species and CO2, and decarboxylation is completely absent for catechol (CAT) and hydroquinone (HYD). 18 Similar isomer-selective reactivity was also observed for xylyl radicals.…”
Section: Introductionmentioning
confidence: 99%